Working with loss and grief a theoretical and practical approach - Machin, Linda (SAGE, 2014)
This updated second edition of Working with Loss and Grief provides a model for practitioners working with those who are grieving a significant life loss. Making clear connections between theory and practice, the 'Range of Response to Loss' model provides a theoretical 'compass' for recognising the wide variability in reaction to loss and the 'Adult Attitude to Grief' scale is a tool for 'mapping' individual grief and its change over time, providing an individual grief profile. Together these offer a framework for practitioners to: -listen to stories of grief told by clients -identify common patterns in grief -recognize individual difference in grief response -make assessments -prompt therapeutic dialogue -guide therapeutic focus and -evaluate outcomes. This edition includes: a new chapter on 'The RRL Model and ..